Resisting Bullying: Narratives of Victims and Their Families - Khanna, Savitri (Université d'Ottawa / University of Ottawa, 2013)
Bullying has severe consequences for school-aged adolescents who have experienced repeated victimization and for the families as well. While there is a considerable body of research on bullying and its effects on victims, very little research has been devoted to studying the experiences and resistance of the targeted young people and their families in the bullying situations. The literature on bullying characterizes victims as unable to defend themselves; this depiction is limited, simplistic, and one-dimensional. This dissertation presents an alternate view, focusing on the experiences and responses of victims and their families. The thesis draws on a poststructural view and a response-based framework to present a new perspective on the victims of bullying—a perspective that contrasts with the common depiction of “helpless, powerless victims” and foregrounds the personal agency of young people who have responded to bullying. Data for this study was collected in the form of narratives from the families and eleven to fifteen year old school adolescents who have been targets of ongoing bullying. The sample consisted of four families and five adolescents. The interview questions were based on Allan Wade’s response-based approach. The participants’ narratives focused on their responses to bullying. Each narrative was read thoroughly for themes related to the skills and the knowledge adolescents have used in responding to peer aggression. Similarly, parents’ narratives were examined for themes of their responses to the bullying of their children. The conclusion from the findings indicated that the parents and adolescents responded to bullying in many small but prudent and resourceful ways.
Keywords: Resistance; Responses; Bullying; Victimization; Narrative Inquiry; Narratives